2010
DOI: 10.1364/oe.18.022485
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast all-optical modulator with femtojoule absorbed switching energy in silicon-on-insulator

Abstract: We demonstrate an all-optical switch based on a waveguide-embedded 1D photonic crystal cavity fabricated in silicon-on-insulator technology. Light at the telecom wavelength is modulated at high-speed by control pulses in the near infrared, harnessing the plasma dispersion effect. The actual absorbed switching power required for a 3 dB modulation depth is measured to be as low as 6 fJ. While the switch-on time is on the order of a few picoseconds, the relaxation time is almost 500 ps and limited by the lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Nevertheless, due to the industrially increasing interest in optics communication the field of all-optical modulation is becoming more and more popular [3][4][5][6][7]. The most important restriction in designing the all-optical modulator is the desire to realize it on Silicon (Si) in order to allow its integration with microelectronic circuitry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, due to the industrially increasing interest in optics communication the field of all-optical modulation is becoming more and more popular [3][4][5][6][7]. The most important restriction in designing the all-optical modulator is the desire to realize it on Silicon (Si) in order to allow its integration with microelectronic circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…They used Silicon-On-Insulator (SOI) ring resonator and in order to get the optical effect they shone with pump power of 25 pJ. Schönenberger et al [5] demonstrated SOIs devices which have reached power requirements of 6 fJ for 3 dB modulation depth with a switch-on time of few picoseconds and recovery time limited by the free charge carriers (FCC) life time being 500 ps. It should be noted that similar works were also done with different materials such as the CMOS compatible amorphous silicon [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this device decreasing its size reduces the power requirement without increasing the Q factor of the device and managed to reduce its modal volume to 6 µm. Ultrafast silicon on insulator (SOI) all optical modulators which require only 6 fJ and operate with response rate of only few ps [8] have also been recently suggested. Reed provided a short review of some prominent silicon based modulators [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is another technique to modulate light beam through the use of another beam in lieu of the aforementioned way. This technique is called all optical modulation (AOM) [2], [3]. A basic material for already existing electronic circuits which can be the perfect candidate for this process as part of an integrated information transferring device is the Silicon (Si).…”
mentioning
confidence: 99%